Efforts to Improve High School Students' Activities and Learning Outcomes on the Human Reproductive System Material with the Implementation of Problem Based Learning Assisted by "GenzB" - Aulia, Nadia; Christijanti , Wulan (Journal of Biology Education, 2024)
The purpose of this study was to improve student activity and learning outcomes, to determine the implementation of learning and the relationship between activity and learning outcomes in the human reproductive system material using the “GenzB” assisted PBL model. This study used an experimental method with a One Group Pre-Post Design. The sample of this study was class XI 1 and XI 2 at SMA Negeri 1 Cikarang Timur. Data collection techniques were by using test techniques including giving pretest posttest questions, and non-test techniques including student activity observation sheets, learning implementation observation sheets and student response questionnaires. The results showed an increase in student activity in each meeting in both experimental classes, namely 66%, 70%, 73% for the average experimental class 1, then 61%, 66%, 71% for experimental class 2, student learning outcomes with N-Gain for both classes were 0,62 (moderate) and 0,60 (moderate), person correlation value of 0,406 with a fairly strong interpretation, learning implementation that obtained a very good category and positive student responses to learning. Based on the research data, it can be concluded that the use of the “GenzB “ assisted PBL model is able to increase student activity and learning outcomes, achieve good implementation and there is a relationship between student activity and learning outcomes in the human reproductive system material.